Effects of melatonin and lactulose on the liver and kidneys in rats with obstructive jaundice - Bülbüller, N; Akkus, MA; Çetinkaya, Z; Ilhan, YS; Özercan, I; Kirkil, C; Dogru, O (Springer-Verlag, 2002)
The negative effects of obstructive jaundice (OJ) on the liver and kidneys cause high morbidity and mortality. In this study, the effects of melatonin (M) and lactulose (L) on the liver and kidneys were investigated by inducing OJ in 30 rats in five groups (n = 6): controls, sham, M, L, and M + L. In the treatment group, after the rats' biliary canals were tied and cut, 10 mg/kg M IM and 2 ml/day L p.o. was administered for 7 days. The histopathologic findings in the liver and kidneys, tissue malonyl dialdehyde (MDA) levels, and serum biochemistry were evaluated. In the M group, pathological histologic findings were less marked than in the other groups; investigation of kidney cross-sections revealed no significant differences among groups. In the jaundiced rats liver MDA levels were significantly higher compared to the control group (P < 0.001), but no such difference was observed in kidney MDA levels (P > 0.05). L did not cause any significant changes in tissue MDA levels. There were no differences among groups with regard to serum levels of liver enzymes and bilirubin. Serum urea was significantly less in the group that received L (P < 0.001), but the groups showed no significant differences with respect to creatinine values (P > 0.05). The increase in serum total cholesterol was significantly less in the M + L group than in the other groups (P < 0.001). We conclude that in the rats in which obstructive jaundice was induced, M administration reduced liver and kidney injury, but L and M + L did not lead to significant improvement.
Keywords: obstructive jaundice; melatonin; lactulose